2018
DOI: 10.1017/ssh.2018.21
|View full text |Cite
|
Sign up to set email alerts
|

Racial Segregation and Southern Lynching

Abstract: The literature on ethnic fractionalization and conflict has yet to be extended to the American past. In particular, the empirical relationship between racial residential segregation and lynching is unknown. The existing economic, social, and political theories of lynching contain implicit hypotheses about the relationship between racial segregation and racial violence, consistent with more general theories of social conflict. Because Southern lynching occurred in rural and urban areas, traditional urban measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…One complication is that the violence begins after Redemption starts, and another is the question of how such persistent political power coincided with black officeholding, which should be less common in areas with a persistent ruling elite. Cook et al (2016) find no effects of black political leadership on lynchings in the Jim Crow era.…”
Section: The Political Ideology Of Black Policymakersmentioning
confidence: 75%
See 1 more Smart Citation
“…One complication is that the violence begins after Redemption starts, and another is the question of how such persistent political power coincided with black officeholding, which should be less common in areas with a persistent ruling elite. Cook et al (2016) find no effects of black political leadership on lynchings in the Jim Crow era.…”
Section: The Political Ideology Of Black Policymakersmentioning
confidence: 75%
“… See Larsen (2015), for example, who estimates death rates for seven confederate states. 14Larsen (2015) argues that Confederate death rates were negatively related to lynching Cook et al (2016),. however, find no evidence that lynching was related to the presence of black politicians during Reconstruction.15 This is not an issue of the quality of the leadership, but whether there were unfilled positions.16 See above for more on the correlation of free blacks with other variables.…”
mentioning
confidence: 99%
“…Several studies have identified the relationship between lynching and black/ white residential segregation as significant. both Defina and hannon (2011) and Cook, Logan, and Parman (2018) demonstrated that higher rates of lynching are positively and statistically significantly related to higher rates of current residential segregation. beyond the statistical relationship, lynching and violent forms of racial social control were intentionally used by whites to maintain geographically defined boundaries (Tolnay and beck 1992).…”
Section: Lynching and Residential Segregationmentioning
confidence: 91%
“…This violence resulted in the physical relocation of many from these communities (Zucchino 2020). Residential segregation offers a useful case for the current analysis, as it impacts social, economic, and political patterns and outcomes (Cook, Logan, and Parman 2018). The socio-spatial position of individuals in neighborhoods influences everything-from exposure to environmental racism, to crime and policing, to access to education and other public services, and capacity for wealth accumulation to name a few (Crowder and Downey 2010;Krivo, Peterson, and Kuhl 2009;flippen 2004).…”
Section: Lynching and Residential Segregationmentioning
confidence: 99%
“…A version of this model is formally laid out in Hsieh et al (2019) and sketched in Rothwell (2019). As applied to the Jim Crow era, this work builds on Parman (2017), andCook, Logan, andParman (2018), who find that residential segregation was much higher in the U.S. South in 1880 and 1940 and that segregation was correlated with worse health outcomes for Black Americans and the probability of being lynched.…”
Section: Introductionmentioning
confidence: 99%